Data-exchange standards and international organizations adoption and diffusion - Thomas, Josephine Wapakabulo, 1976-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
Despite the significance and potential benefits of data-exchange standards, a void remains in literature of a research publication dedicated to its barriers and critical success factors. This book establishes factors related to the implementation and dissemination of data-exchange standards. Written by an international collaboration of field experts, it covers advanced topics such as product life cycle support, IT standardization, and innovation- and adopter-centric data analysis.
General Introduction -- Benefits, Classifications and Research Surrounding Standardization and IT Standards -- IT Standards Adoption and Diffusion Models -- Introduction -- Research Philosophy and Strategy -- Adoption and Diffusion Case Studies -- Innovation-Centric Perspective: ISO Technical Committee 184 Sub-Committee 4 -- Adopter-Centric Perspective: The United Kingdom Ministry of Defence -- Adoption and Diffusion Checklists -- Emergent Innovation-Centric and Adopter-Centric Checklists -- Innovation-Centric Checklist Application: Product Life Cycle Support Adoption and Diffusion -- Adopter-Centric Checklist Application: Product Life Cycle Support Adoption and Diffusion in the UK MoD -- Summary and Recommendations.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on May 24, 2010).
Keywords: Data transmission systems -- Standards; Adopter-centric adoption; Adopter-centric adoption checklist; Adopter-centric data analysis; Adopter-centric diffusion; Data-exchange standards; Innovation-centric adoption checklist; Innovation-centric data analysis; Innovation-centric models; Product life cycle support adoption; Standardization and IT standards; Electronic books